Durable field resistance to wheat yellow mosaic virus in transgenic wheat containing the antisense virus polymerase gene. Issue 4 (27th December 2013) - Chen, Ming; Sun, Liying; Wu, Hongya; Chen, Jiong; Ma, Youzhi; Zhang, Xiaoxiang; Du, Lipu; Cheng, Shunhe; Zhang, Boqiao; Ye, Xingguo; Pang, Junlan; Zhang, Xinmei; et al.
Summary Wheat yellow mosaic virus (WYMV) has spread rapidly and causes serious yield losses in the major wheat‐growing areas in China. Because it is vectored by the fungus‐like organism Polymyxa graminis that survives for long periods in soil, it is difficult to eliminate by conventional crop management or fungicides. There is also only limited resistance in commercial cultivars. In this research, fourteen independent transgenic events were obtained by co‐transformation with the antisense NIb8 gene (the NIb replicase of WYMV) and a selectable gene bar. Four original transgenic lines (N12, N13, N14 and N15) and an offspring line (N12‐1) showed high and durable resistance to WYMV in the field. Four resistant lines were shown to have segregated and only contain NIb8 (without bar) by PCR and herbicide resistance testing in the later generations. Line N12‐1 showed broad‐spectrum resistance to WYMV isolates from different sites in China. After growing in the infested soil, WYMV could not be detected by tissue printing and Western blot assays of transgenic wheat. The grain yield of transgenic wheat was about 10% greater than the wild‐type susceptible control. Northern blot and small RNA deep sequencing analyses showed that there was no accumulation of small interfering RNAs targeting the NIb8 gene in transgenic wheat plants, suggesting that transgene RNA silencing, a common mechanism of virus‐derived disease resistance, is not involved in the process of WYMV resistance. This durable and broad‐spectrum resistance to WYMV in transgenic wheat will be useful for alleviating the damage caused by WYMV.